2012
DOI: 10.1080/07315724.2012.10720022
|View full text |Cite
|
Sign up to set email alerts
|

Cross-Sectional Exploration of Maternal Reports of Food Neophobia and Pickiness in Preschooler-Mother Dyads

Abstract: Preschoolers' food neophobia and pickiness were correlated. Mothers and children displayed similarities in food neophobia, pickiness, and dietary habits. Genetics and environmental cues jointly contribute to shape preschoolers' attitudes toward familiar and unfamiliar foods. Hence, future longitudinal studies of larger samples are necessary to better define the role of genetics, parental feeding practices, and environmental characteristics in the development of food neophobia and pickiness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
100
2
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(114 citation statements)
references
References 39 publications
3
100
2
3
Order By: Relevance
“…A study investigating the effect of infant feeding practices on picky eating in 2e3-year-old children, by Shim et al (2011) found that exclusive breast-feeding for 6 months and the introduction of complementary foods after 6 months of age reduced the odds of picky eating in early childhood. In contrast, Finistrella et al (2012) found no difference in neophobia or pickiness scores between children who were breast-fed or formula-fed, or a mixture of both. They also noted that there was no association of weaning age with the scores.…”
Section: Early Feedingmentioning
confidence: 57%
See 1 more Smart Citation
“…A study investigating the effect of infant feeding practices on picky eating in 2e3-year-old children, by Shim et al (2011) found that exclusive breast-feeding for 6 months and the introduction of complementary foods after 6 months of age reduced the odds of picky eating in early childhood. In contrast, Finistrella et al (2012) found no difference in neophobia or pickiness scores between children who were breast-fed or formula-fed, or a mixture of both. They also noted that there was no association of weaning age with the scores.…”
Section: Early Feedingmentioning
confidence: 57%
“…Maternal healthy eating behaviour has been associated with lower child food fussiness (Gregory, Paxton, & Brozovic, 2010). Although some studies report a higher intake of energy (Finistrella et al, 2012) or energy-dense foods such as savoury snacks and sweets (Tharner, Jansen, Kiefte-de Jong, Moll, & van der Ende, 2014) among children who are picky eaters, most report that picky eating is likely to lead to a reduction in overall food consumption and a distortion of the nutrient composition of the diet through lack of variety [reduced energy intake (Cardona Cano et al, 2015;Carruth, Ziegler, Gordon, & Barr, 2004;Jacobi et al, 2003;Volger et al, 2013); lower intake of fruits and vegetables Galloway, Fiorito, Lee, & Birch, 2005;Haszard, Skidmore, Williams, & Taylor, 2014;Horodynski, Stommel, Brophy-Herb, Xie, & Weatherspoon, 2010;Jacobi et al, 2003;Tharner et al, 2014); lower intake of vitamins and minerals (Cardona Cano et al, 2015;Carruth et al, 2004;Galloway et al, 2005); and lower intakes of whole grain products and dietary fibre (Galloway et al, 2005)]. This can lead to a higher risk of being underweight and having poor growth (Dubois, Farmer, Girard, Peterson, & Tatone-Tokuda, 2007;Ekstein, Laniado, & Glick, 2010;Jansen et al, 2012;Kwok, Ho, Chow, So, & Leung, 2013;Sleddens, Kremers, & Thijs, 2008;Viana, Sinde, & Saxton, 2008;Webber, Hill, Saxton, Van Jaarsveld, & Wardle, 2009), or of being overweight (Finistrella et al, 2012), or of developing eating disorders (Marchi & Cohen, 1990).…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, given that food neophobics who limit their consumption of fruit and vegetables may replace them with foods that are more energy-dense, neophobia may also increase energy intake. Indeed, a recent study observed higher food neophobia in overweight/obese children than in those of normal weight (24) . A small correlation (r = 0·15) between food neophobia and BMI has been observed consistently in young adult women, although not in men (5) .…”
Section: Food Neophobia Diet Quality Steps Study Vegetable Consumptionmentioning
confidence: 99%
“…No standardized or widely followed diagnostic cut-off values exist for classifying individuals as 'food neophobics' and 'food neophilics' based on their FNS score (12) . Often the sample mean (or median) FNS score (18,24,(27)(28)(29) , or the score 35 (30) , has been used as the cut-off value to categorize study participants into two groups. Another common practice is to use the mean plus/minus one standard deviation as cut-off values (11,14,31,32) to form three groups.…”
Section: Food Neophobiamentioning
confidence: 99%
“…Although there is no operational definition of picky eating, the behavior is often characterized by strong food preferences and rejection of familiar or new foods [2]. Picky eating may influence the risk of both underweight and overweight [3,4], development of functional gastrointestinal distress [5] and eating disorders later in childhood [6]. In addition, picky eating in children is associated with emotional and behavioral problems, such as depression, anxiety, and somatic complaints [7,8].…”
Section: Introductionmentioning
confidence: 99%